2000
DOI: 10.1111/j.1651-2227.2000.tb00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone isoenzyme of serum alkaline phosphatase and serum inorganic phosphate in metabolic bone disease of prematurity

Abstract: A combination of the criteria "serum total alkaline phosphatase activity above 900 IU/l" and "serum inorganic phosphate concentrations below 1.8 mmol/l" yielded a sensitivity of 100% at a specificity of 70%. This was the best available screening method for low bone mineral density in preterms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(64 citation statements)
references
References 30 publications
2
60
2
Order By: Relevance
“…39 Although urinary excretion of calcium and phosphate were not related to QUS in our study, AP correlated inversely with QUS, which confirms reports applying both QUS and DXA that found AP to predict reduced bone density with a sensitivity of 88% and a specificity of 71%. 14,15,40,41 The lack of correlation between AP or QUS and serum levels of calcium or phosphate in our patients is most likely due to the stringent regulation of these two minerals by a complex endocrine system to keep their serum levelFessential for many organ functionsFwithin normal limits. As expected, several risk factors for reduced bone formation showed a relevant influence on QUS, that is, the duration of parenteral nutrition or mechanical ventilation and the treatment with diuretics or corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…39 Although urinary excretion of calcium and phosphate were not related to QUS in our study, AP correlated inversely with QUS, which confirms reports applying both QUS and DXA that found AP to predict reduced bone density with a sensitivity of 88% and a specificity of 71%. 14,15,40,41 The lack of correlation between AP or QUS and serum levels of calcium or phosphate in our patients is most likely due to the stringent regulation of these two minerals by a complex endocrine system to keep their serum levelFessential for many organ functionsFwithin normal limits. As expected, several risk factors for reduced bone formation showed a relevant influence on QUS, that is, the duration of parenteral nutrition or mechanical ventilation and the treatment with diuretics or corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are no data demonstrating clinical utility of measuring serum osteocalcin concentration and bone-specific APA in neonates, and normal values do not exist for preterm infants. Backstrom et al 19 found no additional information gained from measurement of bone-specific APA compared with total APA in preterm infants. It is, therefore, unlikely that these laboratory values, which are poorly standardized in neonates and expensive to obtain, will be a substantial aspect of clinical decisionmaking in an individual infant.…”
Section: In-hospital Assessment and Managementmentioning
confidence: 99%
“…Backstrom et al (25) reported that a serum ALP value above 900 U/L was related with low bone mineral density, its sensitivity was 88% and specificity was 71% and a serum P level of <5,5 mg/dL was related with low bone mineral density and its sensitivity was 96% and specificity was 50%. Glass et al (26) reported that an ALP value of >900 IU/l had a sensitivity of 100% in the diagnosis of osteopenia and combination of an ALP value of >800 IU/dL and a P value of <3.5 mg/dL defined severe osteopenia.…”
Section: Discussionmentioning
confidence: 99%